HUBUNGAN PEMAKAIAN KB SUNTIK 3 BULAN DENGAN GANGGUAN HAID PADA WANITA USIA SUBUR DI PMB EKA YUSNIA WULANDARI KABUPATEN LUMAJANG - Alfia, Siti Nur; Alfitri, Rosyidah; Sulistiyah, Sulistiyah (NHM PRESS, 2024)
The use of 3-monthly injectable contraceptive (Kb Suntik 3 Bulan) may cause menstrual disorders, such as shorter or even absent menstruation. This change is in line with the decrease in menstrual blood due to the use of Kb Suntik 3 Bulan. After long-term use, the amount of menstrual blood decreases and amenorrhea may occur. This study aims to determine the Relationship between the Use of 3-Monthly Injectable Contraceptive and Menstrual Disorders in Women of Childbearing Age at Eka Yusnia Wulandari Primary Health Center, Lumajang Regency.This research method employed quantitative research with a quantitative analytical design using a cross-sectional study design, with a total of 35 respondents selected through total sampling technique. The results of the study showed that the majority of respondents were users of Kb Suntik 3 Bulan, amounting to 26 respondents (74.3%), and it was found that the majority of respondents experienced menstrual disorders, amounting to 24 respondents (68.6%).From the analysis using the chi-square test, the significance value obtained was α: 0.001, which means that α <0.05, leading to the conclusion that there is a relationship between the use of Kb Suntik 3 Bulan and menstrual disorders in women of childbearing age at Eka Yusnia Wulandari Primary Health Center, Lumajang Regency.The use of Kb Suntik 3 Bulan can cause side effects, one of which is menstrual disorders. This side effect occurs because Kb Suntik 3 Bulan contains synthetic hormones that can affect the natural hormonal balance in the body. Some women may experience changes in their menstrual cycles after starting to use Kb Suntik 3 Bulan, such as cycle length, amount of blood loss, or intensity of other symptoms such as abdominal pain or discomfort.